Erratum: Correction to: Peripheral signaling pathways contributing to non-histaminergic itch in humans (Journal of translational medicine (2023) 21 1 DOI: 10.1186/s12967-023-04698-z) - Fiebig, Andrea; Leibl, Victoria; Oostendorf, David; Lukaschek, Saskia; Frömbgen, Jens; Masoudi, Maral; Kremer, Andreas E.; Strupf, Marion; Reeh, Peter; Düll, Miriam; Namer, Barbara (Journal of Translational Medicine, 2025)
CRIS-Team Scopus Importer:2025-01-31

Peripheral signaling pathways contributing to non-histaminergic itch in humans - Fiebig, Andrea; Leibl, Victoria; Oostendorf, David; Lukaschek, Saskia; Frömbgen, Jens; Masoudi, Maral; Kremer, Andreas E.; Strupf, Marion; Reeh, Peter; Düll, Miriam; Namer, Barbara (Journal of Translational Medicine, 2023)
Background: Chronic itch (chronic pruritus) is a major therapeutic challenge that remains poorly understood despite the extensive recent analysis of human pruriceptors. It is unclear how the peripheral nervous system differentiates the signaling of non-histaminergic itch and pain. Methods: Here we used psychophysical analysis and microneurography (single nerve fiber recordings) in healthy human volunteers to explore the distinct signaling mechanisms of itch, using the pruritogens β-alanine, BAM 8-22 and cowhage extract. Results: The mode of application (injection or focal application using inactivated cowhage spicules) influenced the itch/pain ratio in sensations induced by BAM 8-22 and cowhage but not β-alanine. We found that sensitizing pre-injections of prostaglandin E2 increased the pain component of BAM 8-22 but not the other pruritogens. A-fibers contributed only to itch induced by β-alanine. TRPV1 and TRPA1 were necessary for itch signaling induced by all three pruritogens. In single-fiber recordings, we found that BAM 8-22 and β-alanine injection activated nearly all CM-fibers (to different extents) but not CMi-fibers, whereas cowhage extract injection activated only 56% of CM-fibers but also 25% of CMi-fibers. A “slow bursting discharge pattern” was evoked in 25% of CM-fibers by β-alanine, in 35% by BAM 8-22, but in only 10% by cowhage extract. Conclusion: Our results indicate that no labeled line exists for these pruritogens in humans. A combination of different mechanisms, specific for each pruritogen, leads to itching sensations rather than pain. Notably, non-receptor-based mechanisms such as spatial contrast or discharge pattern coding seem to be important processes. These findings will facilitate the discovery of therapeutic targets for chronic pruritus, which are unlikely to be treated effectively by single receptor blockade.
CRIS-Team Scopus Importer:2023-12-22
Keywords: BAM 8-22; Cowhage; Discharge patterns; Microneurography; Nociceptor; Pruriceptor; Single-fiber recording; Spatial contrast; β-Alanine

Risk of magnetic resonance imaging-induced magnet dislocation for different types of cochlear implants: a single-center retrospective study - Rupp, Robin; Balk, Matthias; Sievert, Matti; Leibl, Victoria; Schleder, Stephan; Allner, Moritz; Iro, Heinrich; Hoppe, Ulrich; Hornung, Joachim; Gostian, Antoniu-Oreste (Journal of Otolaryngology-Head & Neck Surgery, 2023)
Background: When performing magnetic resonance imaging (MRI) in patients with a cochlear implant (CI), complication rates vary widely in the literature. The primary objective of this retrospective study was to determine the prevalence of complications, in particular magnet dislocation, in patients with CI undergoing 1.5 Tesla (T) MRI. As a secondary objective, the prevalence of magnet dislocation for specific cochlear implant device types was elaborated. Methods: In a single-center retrospective study, all patients with a cochlear implant presenting for an MRI examination at 1.5 T at our institution between January 1st, 2010 and December 31st, 2020 were included. Implants with axial and diametrical magnets were included in the study. MRI safety measures were applied before imaging. The prevalence of complications was evaluated. Magnet dislocation rates were calculated for device types with at least 20 MRI exposures. Results: During the study period, 196 MRI examinations were performed in a total of 128 patients, accounting for 149 different implants (21 implanted bilaterally) with a total of 231 implant exposures to MRI (average 1.69 ± 1.57; min. 1, max. 12). Complications were reported in 50 out of 231 cochlear implant exposures (21.6%). Magnet dislocation occurred in a total of 27 cases (11.7%). Dislocation rates were 29.6% for the Cochlear® CI500 series (24 dislocations from 81 exposures), 1.1% for the Cochlear® CI24RE series (1 from 87) and 0% for the MED-EL® Synchrony (0 from 36). The dislocation rate for the CI500 was significantly higher than for the CI24RE (χ2(1) = 26.86; p < 0.001; ϕ = 0.40) or the Synchrony (χ2(1) = 13.42; p < 0.001; ϕ = 0.34). Conclusions: For 1.5 T MRI, the risk of magnet dislocation ranges from 0 to 29.6% and depends on the CI device type. Implants with a diametrical magnet can be considered potentially MRI-safe, whereas in CIs with axial magnets, the CI500 is at high risk of magnet dislocation. Therefore, apart from a strict indication for an MRI and adherence to safety protocols, post-MRI follow-up examination to rule out magnet dislocation is recommended. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-05-05
Keywords: CI24RE; CI500; Cochlear implant; Complication; Magnet dislocation; Magnet repositioning; Magnetic resonance imaging; Synchrony

The G protein-coupled receptor MRGX4 is a novel receptor for bile salts expressed on sensory neurons - Wolf, Katharina; Kühn, Helen; Leibl, Victoria; Gebhardt, Lisa; Glaudo, Markus; Reeh, Peter; Fischer, Michael J. M.; Neurath, Markus; Namer, Barbara; Kremer, Andreas (SWISS MEDICAL WEEKLY, 2021)
CRIS-Team WoS Importer:2022-03-11

Ultrasound in the diagnosis and differential diagnosis of enoral and plunging ranula: a detailed and comparative analysis - Koch, Michael; Mantsopoulos, Konstantinos; Leibl, Victoria; Müller, Sarina Katrin; Iro, Heinrich; Sievert, Matti (Journal of Ultrasound, 2022)
Purpose To develop sonographic criteria for ranula that to allow rapid and precise diagnosis, differentiation between enoral (ER) and plunging ranula (PR), and differential diagnosis from other competing pathologies in this region.Methods Patients who presented with or were referred with ranula between 2002 and 2022 were assessed in a retrospective study. After clinical investigation, ultrasound examinations were performed in all cases. Several sonographic parameters describing the echotexture, shape and size of ranulas, their relationship to important surrounding anatomical landmarks and the characteristic spreading pattern of ERs and PRs were elaborated and evaluated.Results 207 ranulas were included (82.12% ERs and 17.87% PRs). The ranulas were all in close anatomical relationship to the sublingual gland (SLG) and mylohyoid muscle (MM). The echo texture was hypoechoic to anechoic in 97.6% of the lesions. In comparison with ERs, PRs were larger and irregular in shape significantly more often (P = 0.0001). There were significant differences between ERs and PRs in their exact location relative to the SLG (superficial, deep, anterior, each P = 0.0001; posterior, P = 0.03) and level of the MM (above, below, above and below, P = 0.0001 each). The exact extent and plunging pattern were depicted in all PRs, but naturally in none of the ERs.Conclusions The ultrasound criteria developed in this study, confirming previously published results, indicate that ultrasound is an excellent diagnostic tool for diagnosing ranula and differentiating between ERs and PRs.
CRIS-Team WoS Importer:2023-01-20